PENGARUH PEMBERIAN PUPUK HIJAU KIRINYUH (Chromolaena odorata) DAN NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt.) - Ardan Hendrawan; Wardati Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Sweet corn (Zea mayssaccharata Sturt) is widely used because it has a relatively high nutritional content and sugar content so it tastes sweeter than ordinary corn. Efforts to increase the productivity of sweet corn are proper fertilization. One type of organic fertilizer that can be used is green manure. Green manure comes from plant leaves that are immersed in the soil fresh, one of which can be used as green manure, namely kirinyuh (Chromolaena odorata).This study aims to see the effect of the interaction of green manure kirinyuh and NPK on the growth and production of sweet corn plants and to get the best dose which is carried out in the experimental garden of the Faculty of Agriculture, Riau University, Bina Widya Campus KM 12,5 SimpangBaru sub-district, Tampan District, Pekanbaru, lasts for five months, from August to December 2019. The treatments were given first, namely the dose of kirinyuh fertilizer and the second was the provision of NPK fertilizer. From the two factors, 15 combinations wereobtained, each combination was repeated 3 times so that there were 45 experimental plot units. The data obtained were analyzed using variance and followed by Duncan's test at the 5% level. Based on the results of the research that has been carried out, it can be concluded that the administration of kirinyuh 15 ton.ha-1 and75 kg.ha-1 NPK fertilizer is the best treatment in increasing the growth of sweet corn plants. Keywords: Sweet corn, Kirinyuh Fertilizer, NPK Fertilizer